Implementation of an enhanced recovery after surgery protocol for head and neck cancer patients: Considerations and best practices. Issue 2 (6th March 2022) - Prasad, Aman; Chorath, Kevin; Barrette, Louis‐Xavier; Go, Beatrice; Deng, Jie; Moreira, Alvaro; Rajasekaran, Karthik
Abstract: Enhanced recovery after surgery (ERAS) protocols have been developed in numerous surgical specialties as a means of systematically improving patient recovery, functional outcomes, cost savings, and resource utilization. Such multidisciplinary initiatives seek to minimize variability in several aspects of perioperative patient care, helping to reduce inpatient length of hospital stay, complications, and the overall resource and financial burden of surgical care. Head and neck oncology patients stand to benefit from the implementation of comprehensive ERAS protocols, as these patients have complex medical needs that may dramatically impact multiple aspects of their recovery, including breathing, eating, nutrition, pain, speech, swallowing, and communication. Implementing ERAS protocols for head and neck cancer patients may present unique challenges, and require significant interdisciplinary coordination and collaboration. We therefore sought to provide a comprehensive guide to the planning and institution of such ERAS systems at institutions undertaking care of head and neck cancer patients. Key elements to consider in the implementation of successful ERAS protocols for this population include organizing a team consisting of frontline leaders such as nursing staff, medical specialists, and associated health professionals; designing interventions based on systematically evaluated, high‐quality literature; and instituting a clear methodology for regularly updating protocols and auditing the success or potential limitations of a given intervention. Potential obstacles to the success of ERAS interventions for head and neck cancer patients include challenges in systematically tracking progress of the protocol, as well as resource limitations in a given health system. Abstract : Implementation of an enhanced recovery after surgery protocol for head and neck cancer patients: considerations and best practices. Highlights: Enhanced recovery after surgery protocols have been developed in numerous surgical specialties. Head and neck oncology patients may benefit from ERAS given complex medical needs. Keys to ERAS success include a multidisciplinary team, evidence‐based protocols, and re‐evaluation.